Effectiveness of Combined Health Coaching and Self-Monitoring Apps on Weight-Related Outcomes in People With Overweight and Obesity: Systematic Review and Meta-analysis - Han Shi Jocelyn Chew; Nagadarshini Nicole Rajasegaran; Yip Han Chin; W S Nicholas Chew; Kyung Mi Kim (JMIR Publications, 2023)
BackgroundSelf-monitoring smartphone apps and health coaching have both individually been shown to improve weight-related outcomes, but their combined effects remain unclear. ObjectiveThis study aims to examine the effectiveness of combining self-monitoring apps with health coaching on anthropometric, cardiometabolic, and lifestyle outcomes in people with overweight and obesity. MethodsRelevant articles published from inception till June 9, 2022, were searched through 8 databases (Embase, CINAHL, PubMed, PsycINFO, Scopus, The Cochrane Library, and Web of Science). Effect sizes were pooled using random-effects models. Behavioral strategies used were coded using the behavior change techniques taxonomy V1. ResultsA total of 14 articles were included, representing 2478 participants with a mean age of 39.1 years and a BMI of 31.8 kg/m2. Using combined intervention significantly improved weight loss by 2.15 kg (95% CI −3.17 kg to −1.12 kg; P<.001; I2=60.3%), waist circumference by 2.48 cm (95% CI −3.51 cm to −1.44 cm; P<.001; I2=29%), triglyceride by 0.22 mg/dL (95% CI −0.33 mg/dL to 0.11 mg/dL; P=.008; I2=0%), glycated hemoglobin by 0.12% (95% CI −0.21 to −0.02; P=.03; I2=0%), and total calorie consumption per day by 128.30 kcal (95% CI −182.67 kcal to −73.94 kcal; P=.003; I2=0%) kcal, but not BMI, blood pressure, body fat percentage, cholesterol, and physical activity. Combined interventional effectiveness was superior to receiving usual care and apps for waist circumference but only superior to usual care for weight loss. ConclusionsCombined intervention could improve weight-related outcomes, but more research is needed to examine its added benefits to using an app. Trial RegistrationPROSPERO CRD42022345133; https://tinyurl.com/2zxfdpay